Cystitis and peritonitis caused by Staphylococcus xylosus infection in a calf - Rissi, Daniel R.; Elsmo, Elizabeth J.; Sanchez, Susan (Brazilian Journal of Veterinary Pathology, 2015)
Staphylococcus xylosus is a Gram-positive coagulase-negative staphylococcus with hemolytic activity and ability to form biofilms. This organism can be a component of the human skin microbiome, with rare reported cases of opportunistic infections. S. xylosus can be also isolated from the skin of healthy cattle, horses, pigs, dogs, laboratory mice, chickens, and pigeons. Reports of disease caused by S. xylosus are rare in veterinary medicine, with cases of bovine and ovine mastitis and dermatitis, and pneumonia in immunocompromised laboratory mice. This report describes the first case of transmural necrotizing cystitis and secondary peritonitis caused by S. xylosus in a 4-month-old male Holstein calf with a history of acute onset of recumbency and spontaneous death. Gross necropsy findings included marked urinary bladder distention and diffuse reddening, and large amounts of dark red, hemorrhagic contents. In addition, segments of small intestine and mesentery were adhered to the urinary bladder. Histological evaluation revealed transmural necrosuppurative cystitis with secondary peritonitis and intralesional Gram-positive and fewer Gram-negative cocci. Bacterial culture of urine samples yielded heavy growth of S. xylosus.